Psychometrics of a Brief Trauma Symptom Screen for Youth in Residential Care. Issue 5 (23rd August 2019) - Tyler, Patrick M.; Mason, W. Alex; Chmelka, Mary B.; Patwardan, Irina; Dobbertin, Matthew; Pope, Kayla; Shah, Niraj; Abdel‐Rahim, Heba; Johnson, Kimberly; Blair, R. James
Abstract: Trauma screening is an important element for providing trauma‐informed services to youth in residential care. Unfortunately, lack of time and resources may deter clinicians from conducting trauma screening at intake. This study tested the psychometric properties of the Brief Trauma Symptom Screen for Youth (BTSSY), which could be used during intake into residential care. Participants included 572 youth, ages 10–18 years ( M = 14.28 years, SD = 2.31), of whom 58.9% were boys, 78.7% were Caucasian, 51.7% were youth receiving services in residential care, 15.6% were youth with clinical needs, and 32.7% were typically developing youth from the local community. Participants completed the BTSSY; other questionnaires of psychopathology, childhood maltreatment, and symptomology of posttraumatic stress disorder (PTSD); and diagnostic interviews, which were conducted by licensed psychiatrists. The total BTSSY score had a good composite reliability ( CR ) of .80 and was valid based on a significant positive correlation, r = .64, with the UCLA PTSD–Reaction Index. The BTSSY score was also fair, area under the curve = .75, at detecting a diagnosis of PTSD from a psychiatrist. Significant group differences in the BTSSY scores were found between youth with a diagnosis of PTSD and the other two groups, with moderate‐to‐large effect sizes, d s = 0.73–1.22. Preliminary results indicated the BTSSY may be a useful screening tool for identifying youth at residential care intake who may need additional assessment for PTSD. Limitations and implications for future research and practice are discussed. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Psicometría de la escala breve de síntomas de trauma para jóvenes en atención residencial TAMIZAJE BREVE DE SÍNTOMAS DE TRAUMA PARA JOVENES La detección de los traumas es un elemento importante para proporcionar servicios informados en el trauma a los jóvenes en atención residencial. Desafortunadamente, la falta de tiempo y recursos puede impedir a los médicos realizar detección de traumas en el ingreso. Este estudio probó las propiedades psicométricas de la Escala Breve de Síntomas de Trauma para Jóvenes (BTSSY en su sigla en inglés), que podría usarse durante el ingreso a la atención residencial. Los participantes incluyeron 572 jóvenes, de 10 a 18 años ( M = 14.28 años, DE = 2.31), de los cuales 58.9% eran niños, 78.7% eran caucásicos, 51.7% eran jóvenes que recibían servicios de atención residencial, 15.6% eran jóvenes con necesidades clínicas, y 32.7% eran jóvenes con desarrollo normativo de la comunidad local. Los participantes completaron el BTSSY; otros cuestionarios de psicopatología, maltrato infantil, y sintomatología del trastorno de estrés postraumático (TEPT); y entrevistas de diagnóstico, realizadas por psiquiatras calificados. El puntaje BTSSY total tuvo una buena confiabilidad compuesta ( CR en su sigla en inglés) de .80 y fue válido en base a una correlación positiva significativa, r = .64, con el Índice de Reacción del TEPT de UCLA. El puntaje BTSSY también fue favorable, área bajo la curva = .75, al detectar un diagnóstico del TEPT de un psiquiatra. Se encontraron diferencias significativas entre los grupos en los puntajes BTSSY entre los jóvenes con diagnóstico del TEPT y los otros dos grupos, con tamaños del efecto moderados a grandes, d s = 0.73–1.22. Los resultados preliminares indicaron que el BTSSY puede ser una herramienta útil de detección para identificar a los jóvenes que reciben atención residencial y que pueden necesitar una evaluación adicional para el TEPT. Se discuten las limitaciones e implicaciones para futuras investigaciones y la práctica. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Psychometrics of a Brief Trauma Symptom Screen for Youth in Residential Care Traditional Chinese 標題: 用於收容所的青少年簡短創傷症狀篩查表的心理測量特性 撮要: 創傷的篩查，乃為收容所的青少年提供的創傷支援服務中重要的一部分。可惜，時間與資源不足，可能會防礙臨床治療師在人士入住時提供創傷的篩查。青少年簡短創傷症狀篩查表(BTSSY)可供人士在入住收容所前進行。本研究將測試BTSSY的心理測量特性。樣本包含572名青少年，年齡介乎10至18歲 (M = 14.28 歲, SD = 2.31)，當中58.9%為男性，78.7% 為白人，51.7%為使用收容所服務的青少年，15.6%為有臨床治療需要的青少年，32.7%為本地社區內典型成長中的青少年。樣本完成了BTSSY，及有關以下方面的問卷:心理疾病、兒時受虐經歷、創傷後壓力症(PTSD)症狀學;亦接受由合格的精神科醫生執行的診斷式面談。BTSSY總分有.80的良好組成信度(CR)，並且基於跟UCLA的PTSD反應指數有顯著的正向關連(r = .64)，所以屬有效。BTSSY分數在檢測精神科醫生的PTSD診斷方面，亦表現合理，曲線下面積 = .75。被診斷患PTSD的青少年，跟其它兩組樣本在BTSSY分數上有顯著的組別差異，效應量為中至大(ds = 0.73–1.22)。初步的結果反映，BTSSY可能是在青少年入住收容所前，用以找出有可能需要額外的PTSD評估的青少年有用的篩查功具。我們亦討論到是次研究的限制，及對未來研究和治療的暗示。 Simplified Chinese 标题: 用于收容所的青少年简短创伤症状筛查表的心理测量特性 撮要: 创伤的筛查，乃为收容所的青少年提供的创伤支持服务中重要的一部分。可惜，时间与资源不足，可能会防碍临床治疗师在人士入住时提供创伤的筛查。青少年简短创伤症状筛查表(BTSSY)可供人士在入住收容所前进行。本研究将测试BTSSY的心理测量特性。样本包含572名青少年，年龄介乎10至18岁 (M = 14.28 岁, SD = 2.31)，当中58.9%为男性，78.7% 为白人，51.7%为使用收容所服务的青少年，15.6%为有临床治疗需要的青少年，32.7%为本地小区内典型成长中的青少年。样本完成了BTSSY，及有关以下方面的问卷:心理疾病、儿时受虐经历、创伤后压力症(PTSD)症状学;亦接受由合格的精神科医生执行的诊断式面谈。BTSSY总分有.80的良好组成信度(CR)，并且基于跟UCLA的PTSD反应指数有显著的正向关连(r = .64)，所以属有效。BTSSY分数在检测精神科医生的PTSD诊断方面，亦表现合理，曲线下面积 = .75。被诊断患PTSD的青少年，跟其它两组样本在BTSSY分数上有显著的组别差异，效应量为中至大(ds = 0.73–1.22)。初步的结果反映，BTSSY可能是在青少年入住收容所前，用以找出有可能需要额外的PTSD评估的青少年有用的筛查功具。我们亦讨论到是次研究的限制，及对未来研究和治疗的暗示。